A argumentação filosófica: Chaim Perelman e o auditório universal - Marco Antonio Sousa Alves (2005)
The present thesis aims to investigate Perelman´s proposal of a New Rhetoric, and by doing so, it intends to achieve a better understanding of philosophical discourse. The most important objectives of this work are: defining the fundamental concepts and distinctions of a new theory of argumentation; investigating the specificity of philosophical argumentation - through the clarification of the concept of universal audience -: and finnally analyzing the relationship between persuading and convincing and between contextualism and universalism - establishing, therefore, the Perelman´s place in the contemporany debate concerning argumentation. It is pointed out the closeness between Perelman´s and Haberman´s thoughts, as well as the distance between Perelman´s thinking and Rorty´s and Apel´s. It is shown how, depending of the point of view - if it is internal or external to the audience -, philosophy can be regarded as a discourse bounded by a given context or, on the othrer hand, as an open argumentation aiming at the universal.